Konsep dan Praktik Pendidikan Islam dalam al-Qur’an: Studi Tafsir Tarbawi - Rezky Alsyah Ananta A; Nurdin ; Rahmawati; Sitti Fauziah (Gunung Djati Conference Series, 2022)
This study aims to discuss the concept of Islamic education in the Qur'an. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the tarbawi interpretation, while the material object is the concept of education in the Qur'an. The results and discussion of this study indicate that the term education in the verses of the Qur'an according to Tarbawi's interpretation can be formulated from various words with various derivations so as to form a concept of Islamic education which in practice aims to implement mental, intellectual, and physical education for children. Muslim students so that they have mental, spiritual and behavioral maturity as well as broad knowledge that is useful for realizing goodness in human life. This study concludes that the formulation of Islamic education can be extracted from the verses of the Qur'an by using a tarbawi interpretation approach which will produce views and concepts of education which in practice can be distinguished from the implementation of education in general to create a better life for the people in the future.